Answer:
The answer is a. 3x - y = -11
Step-by-step explanation:
Firstly, you must find the gradient. This is found using the following formula:
[tex]\frac{y2 - y1}{x2 - x1}[/tex]
Make sure that the x2 and y2 values are in the same coordinate set:
Let's set (-3 , 2) as y1 and x1,
y1 = 2 and x1 = -3
That means that (-5 , 8) is y2 and x2,
y2 = 8 and x2 = -5
Plug the values in:
[tex]\frac{8 - 2}{-5 - - 3}[/tex]
Simplified:
[tex]\frac{6}{2}[/tex]
Or 3
So the gradient (or slope) is 3
Now, using the following equation of a line formula:
y - y1 = m(x - x1)
Where m is the gradient and y1 and x1 are two coordinates, we can plug these values in:
y1 = 2
x1 = -3
m = 3
y - 2 = 3(x - - 3)
The negative and the subtract makes it a positive:
y - 2 = 3(x + 3)
Now we can multiply the bracket out:
3 * x = 3x
3 * 3 = 9
So:
y - 2 = 3x + 9
The equation is usually in the form:
y = mx + c
So we need to move the -2 over to the other side making it a positive 2:
y = 3x + 9 + 2
y = 3x + 11
Which is the equation of the line.
The one option that this rearranges to is a) because if you move the y over to the 3x, and the + 11 over to the other side, making them both negatives, the result is:
3x - y = -11
So your answer is a.